Bronchiolitis phenotypes identified by latent class analysis may influence the occurrence of respiratory sequelae. Issue 3 (11th January 2022) - Petrarca, Laura; Nenna, Raffaella; Di Mattia, Greta; Frassanito, Antonella; Castro‐Rodriguez, Jose A.; Rodriguez Martinez, Carlos E.; Mancino, Enrica; Arima, Serena; Scagnolari, Carolina; Pierangeli, Alessandra; Midulla, Fabio
Abstract: Background: The heterogeneity of bronchiolitis may imply or reflect a different predisposition to respiratory sequelae. Objective: Our aim was to investigate whether, among infants hospitalized with bronchiolitis, different clinical profiles extracted by latent class analysis (LCA) are associated with different risks of wheezing. Methods: Over 15 consecutive epidemic seasons (2004–2019), we prospectively enrolled infants <1 year hospitalized for the first episode of bronchiolitis in a single tertiary hospital. A detailed clinical questionnaire was filled for each infant. LCA was applied to differentiate bronchiolitis phenotypes, and after hospital discharge, a phone interview was performed annually to record the presence of wheezing episodes. Adjusted multivariate regression analyses were run to investigate the risk of wheezing during 7 years follow‐up according to clinical phenotypes. Results: LCA performed on 1312 infants resulted in a three‐class model. Profile 1 (65.5%): moderate bronchiolitis; Profile 2 (6.1%): severe bronchiolitis; and Profile 3(28.4%): bronchiolitis infants with high eosinophils blood count. At 1 year of follow up, about 50% of children presented wheezing in each profile. Compared to Profile 1, the adjusted odds ratio (OR) of having wheezing episodes was significantly higher in Profile 2 at 2, 3, and 4 years of follow‐up. At 7 years, Profile 3 had an adjusted OR = 2.58, higher than Profile 2 (adjusted OR = 2.29). Conclusions: LCA clearly identified a "moderate", "severe, " and "high eosinophils blood count" bronchiolitis. During the first 4 years after bronchiolitis, the "severe" profile showed the higher risk of wheezing, but after 7 years this risk seems higher in the "high eosinophils blood count" group.